(untitled) (International Nexus Multidisciplinary Research Journal, 2026)
This study examined comparative analysis of principals’ conflict management practice for improving teachers’ job performance in public and private secondary schools in Anambra State, Nigeria. The study was guided by one research question, and one hypothesis was tested at 0.05 level of significance. A descriptive survey research design was adopted with a study population that comprised 13,505 secondary school teachers in Anambra State, made up of 8,258 teachers in public secondary schools and 5,247 teachers in private secondary schools. A sample of 1,351 teachers consisting 825 from public secondary schools and 526 from private secondary schools were drawn using stratified proportionate sampling technique. Researchers’ developed instrument titled “Principals’ Conflict Management Practices for improving Teacher’s job performance Questionnaire” (PCMPITJPQ) which was validated by three experts was used for data collection. The internal consistency of the instrument was ascertained, using Cronbach’s Alpha and this yielded reliability coefficient of 0.78. Mean and standard deviation were used to answer research questions while t-test was used to test hypothesis. The finding of the study revealed among other things that similar staff conflict management practices when adopted by principals of public and private secondary schools would improve teacher’s job performance in Anambra State. The result indicated among others that there is significant difference in the mean ratings of public and private secondary school teachers on the staff conflict management practices adopted by principals for improving their job performance. It is clear that when principals adopt conflict management practices, it reduce chaotic occurrences that would hinder job performance. Based on the findings, it was recommended that the Principals should promote team building activities so as to encourage collaboration among teachers; take disciplinary action against teachers who are involved in unacceptable behaviour, promptly and carefully investigate on matters regarding clash in issues by teachers and also hold regular meetings that allows open communication to discuss and prevent conflicting issues.